The Relationship Between Interpersonal Communication and Assertive Behavior With Intrapersonal Conflict - Katarina Rizky Sri Mumpuni; Suharsono Suharsono; Daniel Purwoko Budi (FAKULTAS DAKWAH UIN SALATIGA, 2023)
Interpersonal communication and assertive behavior with intrapersonal conflict in employees are important factors in the work atmosphere, of one of the state-owned banks. Quantitative method research with multiple linear regression analysis techniques on the three variables. Based on the results of the analysis that have a highly significant negative relationship between interpersonal communication and assertive behavior with intrapersonal conflict in employees, and partially a highly significant negative between interpersonal communication and intrapersonal conflict, and there is no relationship between assertive behavior and intrapersonal conflict in employees at one of the state-owned banks.